Pengaruh Model Pembelajaran Make A Match Berbantuan Media Audio Visual Terhadap Kompetensi Pengetahuan IPS - Wibawa, Ida Bagus; Suadnyana, I Nengah; Sri Asri, I G. A. Agung (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to determine the significant differences in the competence of IPS knowledge group of students who are taught with the learning model of Make A Match audio visual media assisted with groups of students who were taught by the conventional learning model on the students of grade V SD Gugus Budi Utomo Sub-district Denpasar East Year 2016/2017 . The design used in this research is a quasi-experimental research with non-equivalent control group design. The population of this study is all students of grade V SD Gugus Budi Utomo East Denpasar District, amounting to 324 people. The sample is determined by random sampling technique. The sample in this research is VB SDN 1 Kesiman students with 31 students as experiment group and students of VA SDN 6 Kesiman class with 31 students as control group. The data were collected using the test method in the form of a standard multiple-choice objective test. The data obtained were analyzed using the t-test. The results of data analysis obtained ttabel = 5.611 while at the level of significance 5% and dk = 60 obtained ttable = 2,000. Because thitung = 5.611> ttable = 2,000, then Ho is rejected and Ha accepted. This means that there is a significant difference of students' IPS competency which is taught by Make A Match learning with Audio Visual media with students who are taught by conventional learning model.. So it can be concluded that there is influence of learning model Make A Match audio visual media assisted to the knowledge competence of IPS students of grade V SD Gugus Budi Utomo Sub-district of East Denpasar Year lesson 2016/2017.